2017
DOI: 10.1039/c7cp00676d
|View full text |Cite
|
Sign up to set email alerts
|

Thermal mismatch strain induced disorder of Y2Mo3O12 and its effect on thermal expansion of Y2Mo3O12/Al composites

Abstract: Fully dense YMoO/Al composites were prepared by squeeze-casting. Relatively mild conditions of 750 °C/20 min/50 MPa were used in order to avoid reaction of the components. SEM, Raman spectroscopy, XRD and dilatometry were used to characterize the microstructures and morphologies of the composites. Zero thermal expansion was achieved in the temperature range where the thermal mismatch strain was zero. We show that the CTE mismatch of Al and YMoO results in compressive and tensile strains that distort the YMoO l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Specially, the intensity of green UC emission at 530 nm is enhanced by around 4.4-fold when the temperature is boosted from 303 to 583 K, while those of at 553 and 661 nm are boosted by about 1.4-fold and 2.6-fold, respectively. As confirmed in previous literatures, 18,27 one knows that the unit cell volume of the Y 2 Mo 3 O 12 host lattice is reduced with rising the temperature, leading to the declined distance between the sensitizer (i.e., Yb 3+ ) and activator (i.e., Er 3+ ). Consequently, the ET from Yb 3+ to Er 3+ ions is able to be promoted and more desired excited levels are generated (Fig.…”
Section: Uc Emission Performance Of the Resultant Microparticlessupporting
confidence: 69%
See 1 more Smart Citation
“…Specially, the intensity of green UC emission at 530 nm is enhanced by around 4.4-fold when the temperature is boosted from 303 to 583 K, while those of at 553 and 661 nm are boosted by about 1.4-fold and 2.6-fold, respectively. As confirmed in previous literatures, 18,27 one knows that the unit cell volume of the Y 2 Mo 3 O 12 host lattice is reduced with rising the temperature, leading to the declined distance between the sensitizer (i.e., Yb 3+ ) and activator (i.e., Er 3+ ). Consequently, the ET from Yb 3+ to Er 3+ ions is able to be promoted and more desired excited levels are generated (Fig.…”
Section: Uc Emission Performance Of the Resultant Microparticlessupporting
confidence: 69%
“…14,15 Among the NTE compounds, the A 2 Mo 3 O 12 (A presents trivalent cation) has received extensive attention on account of its merits of large chemical flexibility, stable structure, high ion conduction and strong NTE performance. 16,17 Specially, Y 2 Mo 3 O 12 shows the best NTE behaviors with lowest anisotropy since the Y 3+ ions possess relatively bigger ionic radius and smaller electronegativity in comparison with other trivalent cations, 18,19 and thus it has been widely researched as host material. Interesting, Wang et al, revealed that the NTE effect in Yb 2 W 3 O 12 and Sc 2 Mo 3 O 12 compounds was benefit for thermally enhancing the UC emissions of rare-earth ions (i.e., Er 3+ , Ho 3+ , Tm 3+ ) due to the lattice distortion and contraction.…”
Section: Introductionmentioning
confidence: 99%
“…[13,[18][19][20] However, previous experimental studies were mainly focused on in-plane stretch or compression of 2D materials induced by substrate. [21][22][23] Experimentally, the important role of the out-of-plane coupling and its effect on the thermal expansion remain unclear.…”
mentioning
confidence: 99%
“…Several techniques had been applied to TEC measurements of 2D materials, such as the scanning electron microscope, [24] micromechanical resonator, [25] X-ray diffraction, [26] Fabry-Perrot interference, [27] digital image correlation, [28] atomic force microscopy (AFM), [16] transmission electron microscope (TEM), [29] and Raman spectroscopy. [21][22][23][30][31][32] Unfortunately, the reported values of TEC of monolayer graphene diverge, varying from −8.0 × 10 −6 to +1.6 × 10 −6 K −1 at room temperature. [31] As discussed above, the out-of-plane coupling has crucial effect on TEC of 2D material.…”
mentioning
confidence: 99%
“…In order to understand the NTE mechanisms in Y 2 Mo 3 O 12 , several studies have been performed: the relation between AO 6 polyhedral distortion and NTE in orthorhombic Y 2 Mo 3 O 12 [16], and the effect of water species on the phonon modes [11,17]. There are many studies to improve the NTE properties in Y 2 Mo 3 O 12 [18,19], and to characterize various properties of Y 2 Mo 3 O 12 [20][21][22]. These studies have shown that the hygroscopicity is related to the sizes of cations A, and the reduction of hygroscopicity is achieved by substituting trivalent cations to Y 3+ sites [10,23].…”
Section: Introductionmentioning
confidence: 99%